OPTICAL ILLUSION DESIGN BASED ON FOUR CONVEX LENSES SYSTEM AND CLOAKING AREA CHARACTERIZATION (Jurnal Pendidikan Fisika Indonesia, 2018)
A set up of optical illusion based on 4f system and characterization of cloaking area have been carried out. The cloaking area is an area where the object is placed on the area as if it disappears from view; the set-up of cloaking area is located at the top of the third lens. The distance between the lens and the cloaking, which is generated from 4f system, depends on the size of the focal point and the size of the lens used. The larger the focal point of the lens used the wider the distance between the lenses and the larger the size of the diameter of the lens, the cloaking range will be increasingly wide, and vice versa. From the experimental results that we obtained that the cloaking area for set up using FL (focusing lens) 100, 50, 50 and 100 mm with a diameter of 3.6 cm lens is Â± 2 cm, whereas for the set up using lens FL 150, 100, 100 and 150 mm with lens diameter 2.54 cm is Â± 1 cm.